Spectral dynamical behavior in passively mode-locked semiconductor lasers - Stolarz, P.; Javaloyes, J.; Mezosi, G.; Hou, L.; Ironside, Charlie; Sorel, M.; Bryce, A.; Balle, S. (2011)
In this paper, we present an experimental and theoretical study of passive mode-locking in semiconductor Fabry-Pérot, quantum-well, lasers operating at around 1550 nm and producing picosecond pulses at a repetition frequency of 40 GHz. The different regimes that occur as the reverse bias voltage applied to the saturable absorber (SA) section or the bias current injected into the amplifier section are characterized both in the time and frequency/wavelength domains. Our results reveal that the lasers display spectral competition between the gain of the amplifier section and the absorption of the SA, with variations of the lasing wavelength up to 25 nm as the bias conditions are changed. These wavelength variations result from the thermal drift of the SA band-edge due to Joule heating by the generated photocurrent and from the competition between two possible lasing regions placed either at the amplifier gain peak or near the band-edge of the SA. The experimental observations are satisfactorily reproduced and explained in the framework of a Traveling Wave Model complemented by a time-domain description of the semiconductor susceptibility. © 2011 IEEE.